The Influence of Network Position on Executives’ Preference for Imitation over Innovation: A Scenario-Based Experimental Approach - Guojian Zhang; Francis Boadu; Yu Xie (Systems)
This study investigates how the different dimensions of a firm’s network position influence executives’ preference for imitation over innovation in new venture development, thus reflecting their preference for uncertainty. Through a scenario-based experimental approach involving 1024 responses from 64 senior executives, we examine how network centrality, structural equivalence, and structural autonomy shape these strategic preferences. The findings reveal that firms with higher network centrality tend to favor innovation over imitation more strongly. At the same time, those in structurally equivalent positions show a greater preference for imitation. Structural autonomy does not significantly affect these preferences. This study contributes to the literature by revealing how different network structures uniquely influence strategic decision-making in uncertain environments, offering valuable insights for scholars and practitioners. The scenario-based experimental method enhances the precision of the findings and provides actionable implications for real-world decision-making in venture development.